2016
DOI: 10.1098/rstb.2015.0359
|View full text |Cite
|
Sign up to set email alerts
|

Validation and optimization of hypercapnic-calibrated fMRI from oxygen-sensitive two-photon microscopy

Abstract: One contribution of 15 to a Theo Murphy meeting issue 'Interpreting BOLD: a dialogue between cognitive and cellular neuroscience'. LG, 0000-0001-7202-5176Hypercapnic-calibrated fMRI allows the estimation of the relative changes in the cerebral metabolic rate of oxygen (rCMRO 2 ) from combined BOLD and arterial spin labelling measurements during a functional task, and promises to permit more quantitative analyses of brain activity patterns. The estimation relies on a macroscopic model of the BOLD effect that ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…In vivo experiments in humans have found that β=1 in calibrated BOLD experiments at 1.5 T, 3 T, and 7 T, which is consistent with recent multicompartment vascular modeling studies that suggest β=1 at 3 T . These vascular modeling studies estimated β and α indirectly by treating them as free parameters of the Davis model in simulations of the BOLD signals.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In vivo experiments in humans have found that β=1 in calibrated BOLD experiments at 1.5 T, 3 T, and 7 T, which is consistent with recent multicompartment vascular modeling studies that suggest β=1 at 3 T . These vascular modeling studies estimated β and α indirectly by treating them as free parameters of the Davis model in simulations of the BOLD signals.…”
Section: Introductionsupporting
confidence: 81%
“…The microvascular networks used here were obtained using in vivo 2‐photon imaging of the cerebral cortex of C57BL/6 mice and published in previous studies . We used 6 unique microvascular networks obtained from 6 different mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study of this kind is that by Gagnon et al [164]. Gagnon et al used the VAN model, based on the fundamental physiological processes with a microscopic level of detail, to simulate BOLD and ASL signals bottom-up.…”
Section: Human Translationmentioning
confidence: 99%
“…Parcellating cortex in this manner will allow for neuroanatomically valid spatial smoothing of fMRI data and increased statistical power. If these analyses could be combined with information about regional differences in neurovascular coupling and expected BOLD magnitudes [93,94], the power of these new methods could be increased even further, allowing for increased accuracy and validity in understanding functional specialization across the brain.…”
Section: (G) Multi-modal Imaging Approachesmentioning
confidence: 99%